Video-based project as manifestation of Merdeka curriculum in Speaking for General Communication subject: Perspectives and challenges - Hayatul Muna; Ainol Mardhiah; Rusma Setiyana (Universitas Merdeka Malang, 2025)
This study aims to explore students' perceptions and challenges of the video-based projects implementation as a form of Merdeka curriculum in speaking for the General Communication subject. The first-semester students of English Education Department IAIN Lhokseumawe become the subject of this study. Moreover, the data were gained through the distribution of questionnaires and in-depth interviews, which were then analysed descriptively. The research results show that the majority of students responded positively to the use of video-based projects in speaking lessons. Students feel more confident, motivated, and capable of improving their speaking skills as well as other supporting skills such as pronunciation, editing, and scriptwriting. In addition, this project also encourages independence, creativity, and provides a more contextual and meaningful learning experience. However, this study also found several challenges faced by students, such as technical constraints, inadequate equipment, difficulties in scriptwriting, and psychological pressure due to teachers’ expectation. Therefore, technical support, adequate guidance, and adjustments to learning strategies are needed so that the implementation of video-based projects can run more optimally. Overall, video-based projects have proven to be relevant as a constructive and participatory learning method that aligns with the spirit of the Merdeka Curriculum. Keywords: Merdeka Curriculum, project-based learning, speaking skill, video-based project